Foreign Exchange and Forex Markets Transactions: Implementation on Turkey's Economy - Aylin Erdoğdu; Aydın Karamehmet (6th International OFEL Conference on Governance, Management and Entrepreneurship. New Business Models and Institutional Entrepreneurs: Leading Disruptive Change. April 13th - 14th, 2018, Dubrovnik, Croatia, 2018)
Foreign Exchange rate movement is one of the most important indicator for investors decision to invest in the Foreign Exchange and Forex markets. The development of this market and gaining stability of this progress is possible through the investment of the investors. If investors invest keeping in mind the factors affecting market, will make more healthy investment decision. It is of great importance for investors, investing these markets, determination of factors what causes volatility in Foreign Exchange and Forex market. The aim of this study is, explaining all features of the Foreign Exchange and Forex market, determining factors influence to what extend trading volumes of Foreign Exchange and Forex markets. Macro and micro factors which affect the Foreign and Forex markets are dealt with. Two applications were also made using the method of 'Multiple Linear Regression Analysis' to measure the impact of these factors. The research includes applications of multiple linear regression model. In the first application, the data set consists of monthly data for Forex Transaction Volume, between 01.01.2013 - 01.04.2016 date, the second one, the data set consists of monthly data for Foreign Exchange Deposit Account, between 01.01.2006 - 01.05.2016. In the use of the data, at the end of month values are taken into account and obtained from CBRT (Central Bank Of The Republic Of The Turkey), CMB (Capital Markets Board of Turkey) and TCMA (Turkish Capital Market Association) internet sites. In the first analysis, Forex Transaction Volume is used as a dependent variable. In the other analysis; Currency Deposits Account Volume is used as a dependent variable. Independent variables used in both analyzes; USD / TR, gold ons price, inflation (CPI) and BIST Trading Volume. According to the results of the research; the most important factor determining whether affecting dependent variables within the independent variables is U.S dollar. According to the Multiple Linear Regression Model, there is a positive correlation between dollar exchange rate and Forex Transaction Volume and Foreign Exchange Deposits Account Volume. This is a very meaningful and expected result. Because the majority of Forex market transactions are foreign exchange buying and the most denominated currency is US dollar in Turkey, the increase in the currencies will increase the trading volume on the market. As the dollar rallies begin to rise, investors are anticipating trends in this direction and they are shifting their money towards this direction. This trend also leads to an increase in Foreign Exchange Deposit's volume. As a result of the study, the investors, the fields they should invest in and the issues that they should pay attention to are discussed within the scope of the research, and both academic and sectoral information has been given. The main aim of the investors is to achieve a prosperity. For this reason, the risk factor of most of the investments that will take place is the most important place. The risk may increase the return or it may lose all the money. Firstly, the market and investment vehicle must be thoroughly researched and investments should be made at the right time.
Keywords: 650; Foreign exchange market; Forex market; Multiple linear regression analysis; foreign exchange deposit